A Global Survey on Diagnostic, Therapeutic and Preventive Strategies in Intensive Care Unit—Acquired Weakness - Felix Klawitter; Marie-Christine Oppitz; Nicolai Goettel; Mette M. Berger; Carol Hodgson; Steffen Weber-Carstens; Stefan J. Schaller; Johannes Ehler (Medicina, 2022)
Background and Objectives: Intensive care unit-acquired weakness (ICU-AW) is one of the most frequent neuromuscular complications in critically ill patients. We conducted a global survey to evaluate the current practices of diagnostics, treatment and prevention in patients with ICU-AW. Materials and Methods: A pre-survey was created with international experts. After revision, the final survey was endorsed by the European Society of Intensive Care Medicine (ESICM) using the online platform SurveyMonkey®. In 27 items, we addressed strategies of diagnostics, therapy and prevention. An invitation link was sent by email to all ESICM members. Furthermore, the survey was available on the ESICM homepage. Results: A total of 154 healthcare professionals from 39 countries participated in the survey. An ICU-AW screening protocol was used by 20% (28/140) of participants. Forty-four percent (62/141) of all participants reported performing routine screening for ICU-AW, using clinical examination as the method of choice (124/141, 87.9%). Almost 63% (84/134) of the participants reported using current treatment strategies for patients with ICU-AW. The use of treatment and prevention strategies differed between intensivists and non-intensivists regarding the reduction in sedatives (80.0% vs. 52.6%, p = 0.002), neuromuscular blocking agents (76.4% vs. 50%, p = 0.004), corticosteroids (69.1% vs. 37.2%, p < 0.001) and glycemic control regimes (50.9% vs. 23.1%, p = 0.002). Mobilization and physical activity are the most frequently reported treatment strategies for ICU-AW (111/134, 82.9%). The availability of physiotherapists (92/134, 68.7%) and the lack of knowledge about ICU-AW within the medical team (83/134, 61.9%) were the main obstacles to the implementation of the strategies. The necessity to develop guidelines for the screening, diagnosing, treatment and prevention of ICU-AW was recognized by 95% (127/133) of participants. Conclusions: A great heterogeneity regarding diagnostics, treatment and prevention of ICU-AW was reported internationally. Comprehensive guidelines with evidence-based recommendations for ICU-AW management are needed.